2011
DOI: 10.1111/j.1742-4658.2011.08179.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate racemization and catabolism inFusobacterium varium

Abstract: The pathways of glutamate catabolism in the anaerobic bacterium Fusobacterium varium, grown on complex, undefined medium and chemically defined, minimal medium, were investigated using specifically labelled 13C‐glutamate. The metabolic end‐products acetate and butyrate were isolated from culture fluids and derivatized for analysis by nuclear magnetic resonance and mass spectrometry. On complex medium, labels from l‐[1‐13C]glutamate and l‐[4‐13C]glutamate were incorporated into C1 of acetate and equally into C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
(122 reference statements)
0
9
0
Order By: Relevance
“…This pathway (Supplementary Figure S2), involved in fermentation of Glutamate to Acetyl-CoA and finally Butyryl CoA, has been observed in various strains of Fusobacteria (Ramezani et al, 2011). Further analysis in this study on sequenced genomes (data not shown) showed that amongst the butyrate producers, this pathway was observed in Fusobacteria and few pathogenic strains of Clostridium like Clostridium tetani and Clostridium tetanophorum .…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…This pathway (Supplementary Figure S2), involved in fermentation of Glutamate to Acetyl-CoA and finally Butyryl CoA, has been observed in various strains of Fusobacteria (Ramezani et al, 2011). Further analysis in this study on sequenced genomes (data not shown) showed that amongst the butyrate producers, this pathway was observed in Fusobacteria and few pathogenic strains of Clostridium like Clostridium tetani and Clostridium tetanophorum .…”
Section: Resultsmentioning
confidence: 77%
“…Apart from the above mentioned three pathways, previous studies have also reported involvement of methylaspartate pathway in butyrate production in Fusobacterium varium (Ramezani et al, 2011), a pathogen observed in human ulcerative colitis. This pathway (Supplementary Figure S2), involved in fermentation of Glutamate to Acetyl-CoA and finally Butyryl CoA, has been observed in various strains of Fusobacteria (Ramezani et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Fusobacterium sp. which was more prevalent in the women who delivered preterm and within 2 weeks of sampling, ferments glutamate to acetate via the hydroxyglutarate pathway [32, 33]. Such metabolic processes explain our observation that the Ace/Glx ratio was associated with sPTD and delivery within 2 weeks of sampling.…”
Section: Discussionmentioning
confidence: 73%
“…These two pathways have been referred to as ‘histidine degradation’ and ‘THF production’ pathways throughout the manuscript. Further, for the glutamate fermentation pathway (glutamate → acetate + pyruvate) ( Figure 1C ), the third ammonia releasing pathway considered here, a subset of the constituent genes has been reported to occur in genomic context in Fusobacterium varium ( Ramezani et al, 2011 ). The genes encoding two (EC: 5.4.99.1 and EC: 4.3.1.2) out of the four enzymes of the pathway are located in consecutive positions in the F. varium genome ( Ramezani et al, 2011 ).…”
Section: Methodsmentioning
confidence: 78%